Thermocycling influence on iron deformation in hydrogen atmosphere - Толстенко, Александр Васильевич (Eastern-European Journal of Enterprise Technologies, 2012)
This article represents the influence of conditions of polymorphic transformation of iron (0,03 and 0,06% C) on the deformation in a hydrogen atmosphere. Deformation per cycle is determined by the temperature-rate conditions at the front of transformation